Mia Hall's Decision-Making in If I Stay by Gayle Forman Based on Freudian Psychoanalysis Theory - Leonita, Cindy; Kurniawan, Yohanes; Fadillah , Eka (English Department, Universitas Negeri Surabaya, 2021)
This study aims at investigating a decision-making process based on Freudian Psychoanalytic theory in Gayle Forman’s If I Stay. This study specifically focuses on the main character, Mia Hall. Based on Freud’s, all human behaviour, including decision-making, is influenced by the interaction of three structures of personality: Id, Ego, and Superego. This study discussed the interrelation of those structures in affecting Mia’s decision-making process. Furthermore, this study also searched for the prominent domination explicated in Mia’s final decision. The writers applied Freudian Psychoanalysis to reveal the main focus of this study. The compelling utterances and narrations from the novel are considered the primary source of data. Then, the data are classified into Id, Ego, and Superego before looking for the interrelation and dominant structure. Besides Psychoanalytic, this study also applied character and characterization theory to help the writers analyse the utterances and behaviour of Mia. The result reveals that, though the Id, Ego, and Superego have their desire, these three structures can balance each other and eventually lead Mia to a decision. It is crucial to learn and investigate the dynamic of the decision-making process encountered by a human.